The Role of English as a Foreign Language Teachers’ Technological Pedagogical Content Knowledge on English as a Foreign Language Students’ Achievement - Guoxiang Duan; Linlin Jia; Hui Chen (Frontiers in Psychology, 2022)
Educators themselves and their knowledge are the most significant elements in learners’ success and achievement; however, there is little information about the specialized knowledge held by educators. Recently, conceptualizing educator knowledge has become a complicated issue that involves that the comprehension of important basic phenomena, such as the procedure of educating and learning, the notion of knowledge, and the way educators’ knowledge, has become practical within the class. Technological Pedagogical Content Knowledge (TPACK) was presented as a theoretical structure for the knowledge base because educators have to efficiently instruct with technology and it is regarded as a valuable framework for explaining and understanding technology integration into various academic environments, such as English as a Foreign Language (EFL) class. This paper is intended to review the related literature on the role of an English teacher using the TPACK framework for teaching English and their role in students’ achievement. Based on the related literature, there is a significant and direct association between EFL teachers’ TPACK and EFL students’ achievement. Succinctly, some recommendations have been proposed for educational stakeholders.